Pengelolaan Dokumen Kedaluwarsa dalam Sistem Mutu Industri Farmasi: Tantangan dan Solusi - Ucu Hartini; Riska Nurmala; Saeful Amin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Document control is a fundamental requirement in the pharmaceutical industry quality system, explicitly regulated under CPOB 2024 Chapter 10 and ISO 9001:2015 Clause 7.5. Documents that remain in use after their expiration date may cause operational procedures to diverge from actual conditions and may potentially lead to product non-conformities. This article analyzes the phenomenon of expired documents in the PPIC department of salah satu industri farmasi swasta nasional, based on the 2025 Internal Audit results. Six Work Instructions (IK) were found to have passed their review date IK-MM03-005-01, IK-MM03-009-00, IK-MM03-013-00, IK-MM03-014-00, IK-MM03-015-00, and IK-MM03-016-00 with delays ranging from 3 to 18 months, all categorized as Critical findings. Root cause analysis using the Fishbone 6M framework identified the dominant contributing factors as the absence of an automated document expiration monitoring system, the absence of a dedicated document control officer, a masterlist that is not updated in real time, and the absence of document management KPIs. This article recommends a layered solution comprising the implementation of a digital Document Management System, the appointment of a document control officer, masterlist revision, integration of document monitoring into management review, and regular Good Documentation Practice training.